Assessment of fetal lung maturity by ultrasound: objective study using gray-scale histogram. (April 2015) - Beck, Ana Paula Avritscher; Araujo Júnior, Edward; Leslie, Ana Teresa Figueiredo Stochero; Camano, Luiz; Moron, Antonio Fernandes
Abstract Objective: To evaluate lung maturity using ultrasound (US), comparing the subjective and gray-scale histogram (GSH) techniques. Methods: A total of 77 single pregnancies were evaluated and divided into the following two groups: 11 women of gestational age 28 to 35 + 6 weeks and 66 women ≥ 36 weeks. The women underwent to emergency or planned cesarean section, according to fetal–maternal indications. The US was performed on the mean sagittal plane of the fetal torso, in order to observe the lung and hepatic areas. Fetal lung maturity was evaluated subjectively and through GSH. After delivery, the incidence of respiratory distress in the newborn was evaluated. The analyses were considered to be correct or incorrect, and comparisons were made using the McNemar test. In order to compare lung/hepatic echogenicity using GSH in groups with and without respiratory distress, the Student's t-test was used. Results: The subjective evaluation identified 41 cases (53.2%) correctly and 36 (46.8%) incorrectly, while GSH found 58 (75.3%) correctly and 19 (24.7%) incorrectly (p = 0.006). There was a significant difference in mean lung/hepatic echogenicity between the groups with and without respiratory distress (1.05 versus 1.26; p = 0.002). In the group of 28 to 35 + 6 weeks, GSH presented sensitivity, specificity and accuracy in predicting respiratory distress of 61.9%, 89.1% and 81.6%, respectively. Conclusion: The evaluation of fetal lung maturity through GSH was more effective than the subjective method in predicting respiratory distress among newborns.